An efficient capuchin search algorithm for extracting the parameters of different PV cells/modules - Ali, Hossam Hassan; Fathy, Ahmed; Al-Dhaifallah, Mujahed; Abdelaziz, Almoataz Y.; Ebeed, Mohamed (Frontiers in Energy Research, 2022)
Constructing an equivalent circuit for the photovoltaic (PV) generating unit converging the real operation is difficult process as a result of unavailability of some parameters. Many approaches have been conducted in this field however they have some problems in computational time and stuck in local optima. Therefore, this paper proposes simple, robust, and efficient methodology incorporated capuchin search algorithm (CapSA) to construct the equivalent circuit of the PV generating unit via identifying its parameters. The CapSA is selected as it is simple and requires less computational time in addition to exploration/exploitation balance that avoids local optima. The process is formulated as optimization problem which aimed at minimizing the root mean square error (RMSE) between the measured and simulated currents. Single diode model (SDM), double diode model (DDM), and three diode model (TDM) of different PV cells and panels operated at either constant or variable weather conditions are constructed. A comparison to different programmed metaheuristic approaches is conducted. The best RMSE values obtained by the proposed CapSA are 2.27804E-04, 1.3808E-04, and 1.5182E-04 for SDM, DDM, and TDM of PVW752 cell. For KC200GT panel, the proposed approach acheived the best fitness values of ‎3.4440E-04‎, ‎1.5617E-03‎, and ‎6.6008E-03‎ at 25 ºC, 50 ºC, and 75 ºC respectively. The obtained results confirmed the superiority and competence of the proposed CapSA in constructing reliable equivalent circuit for the PV cell/panel.